(untitled) (Conferencea, 2022)
The article presents the views of some lawyers on the concept of simplified legal proceedings in criminal procedure relations and specific criteria for simplified legal proceedings, comparison of the rules of simplified legal proceedings in the criminal procedure legislation of some foreign countries, scientific and theoretical aspects. Based on the results of the study, suggestions and recommendations were made for the broad implementation of positive experience in our national legislation, the introduction of simplified procedures in criminal proceedings.